2022
DOI: 10.2528/pier22051601
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning-Enabled Recovery of Prior Information From Experimental Breast Microwave Imaging Data

Abstract: We demonstrate the recovery of simple geometric and permittivity information of breast models in an experimental microwave breast imaging system using a synthetically trained machine learning workflow. The recovered information consists of simple models of adipose and fibroglandular regions. The machine learning model is trained on a labelled synthetic dataset constructed over a range of possible adipose and fibroglandular regions and the trained neural network predicts the geometry and average permittivty of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Recently, deep learning is poised to expedite on-demand photonic design and mitigate the imperfections in conventional methods 17 22 Its unique advantages lie in the data-driven nature to allow a computational model to discover useful information from given data and thus carry out tasks without explicit programmed and procedural instructions. The past decade has witnessed a proliferation of deep-learning-enabled forward/inverse design, spectral correlation, intelligent metadevices, and latent physics discovery with different network architectures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, deep learning is poised to expedite on-demand photonic design and mitigate the imperfections in conventional methods 17 22 Its unique advantages lie in the data-driven nature to allow a computational model to discover useful information from given data and thus carry out tasks without explicit programmed and procedural instructions. The past decade has witnessed a proliferation of deep-learning-enabled forward/inverse design, spectral correlation, intelligent metadevices, and latent physics discovery with different network architectures.…”
Section: Resultsmentioning
confidence: 99%
“…For a customer-defined cloaking effect, brute-force search in tandem with lengthy case-by-case full-wave simulations is suboptimal because it inevitably degrades the working efficiency of the invisibility cloak 17 22 So far, although deep learning has been substantially applied for the inverse design of subwavelength meta-atoms, the generalization to the entire large-scale metadevices is not readily followed due to the dimensional curse and intractable nonuniqueness issue. Third, a fully self-driving intelligent cloak necessitates the buildup of a highly complex perception–decision–execution system, including full-context awareness of incoming waves and environment, and the attitude recognition of cloak 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Edward et al 139 demonstrated the impressive ability of a neural network, trained using synthetic data, to analyze experimental data through parametric inversion accurately. This neural network effectively extracted relevant prior knowledge, such as the geometry and average complex-valued permittivity, which are crucial for understanding the fibroglandular tissue in a simplified model of the human breast.…”
Section: State-of-art Techniques Of Ai-assisted Mwi In Disease Diagnosismentioning
confidence: 99%
“…To address nonlinearity, deep learning (DL) solutions have been developed extensively [30]- [35]. These studies have shown that such nonlinear issues can be effectively optimized, even in full-wave 3D models or experimental setups [36]. However, the accuracy of the DLbased approach is largely dependent on both the pre-training dataset and the DL structure.…”
Section: Introductionmentioning
confidence: 99%